Emerging pharmaceutical contaminants in key aquatic environments of the Philippines - Mariano, Shyrill Mae F.; Angeles, Luisa F.; Aga, Diana S.; Villanoy, Cesar L.; Jaraula, Caroline Marie B. (Frontiers in Earth Science, 2023)
Pharmaceuticals in natural waters are considered emerging pollutants due to their low concentrations and the negative effects they pose to the environment. Common sources of such pollutants include untreated wastewater from hospitals, residential, industrial, and agricultural sources. Many wastewater treatment methods only remove a subset of all pharmaceuticals from the wastewater; remaining pharmaceuticals are discharged into natural waters, and ultimately drain into coastal areas. Regions without proper wastewater treatment are especially susceptible to such contamination. This study deals with the distribution, sources, and seasonal variability of pharmaceuticals in key aquatic systems in the Philippines. Two watershed continuums (Davao Gulf, Davao City; Macajalar Bay, Cagayan de Oro City); two tourist areas (Boracay Island, Aklan; Mabini, Batangas); and one pristine atoll (Tubbataha Reefs, Palawan)—all with varied prevailing human population pressures—were studied. Samples of hospital wastewater as well as groundwater, surface and bottom water samples from rivers and coastal seas collected during dry and wet seasons were analyzed using solid-phase extraction and liquid chromatography-tandem mass spectrometry. Thirty-four target pharmaceutical residues and antibiotics were extracted and quantified. Acetaminophen was detected at concentrations of up to 289.17 ppb in freshwater samples, and at concentrations of up to 253.39 ppb in seawater samples. Ubiquitous to all the sites was caffeine, reaching 1848.57 ppb. Sulfamethazine, a commonly used veterinary antibiotic, was detected at 764.91 ppb in a river site in Cagayan de Oro. Untreated hospital wastewater contained metformin, iopamidol, sulfamethoxazole, acetylsulfamethoxazole, ciprofloxacin, and azithromycin, but these pharmaceuticals were not detected in other river and coastal waters. Samples collected during the dry season exhibited higher concentrations than those from the wet season, which appears to be related to increase in transient populations from tourism activities as well as dilution. The presence of pharmaceutical residues and antibiotics in these areas and the potential impact on the environment indicate the need for stricter wastewater management measures, particularly in communities located near water bodies. As the results of this study show, such measures might be most beneficial and effective if imposed during dry season and in areas open to tourism.